Glycoproteins C and D of PRV Strain HB1201 Contribute Individually to the Escape From Bartha-K61 Vaccine-Induced Immunity - Ren, Jianle; Wang, Haibao; Zhou, Lei; Ge, Xinna; Guo, Xin; Han, Jun; Yang, Hanchun (Frontiers in Microbiology, 2020)
The newly emerged pseudorabies virus (PRV) novel variants can escape from the immunity induced by the classical vaccine Bartha-K61. Here we investigated the underlying mechanisms by constructing chimeric mutants between epidemic strain HB1201 and the Bartha-K61 vaccine. Our analyses focused on three viral envelope glycoproteins, namely gB, gC, and gD, as they exhibit remarkable genetic variations and are also involved in induction of protective immunity. The corresponding genes were swapped reciprocally either individually or in combination by using CRISPR/Cas9 technology and homologous recombination. The rescued chimeric viruses exhibited differential sensitivity to neutralizing antibodies in vitro, and gC was found to be the major contributor to inefficient neutralization against HB1201 by anti-Bartha-K61 serum. When tested in the 4-week-piglet model, substitution with HB1201 gC enabled Bartha-K61 to induce a protective immunity against HB1201 at a high challenge dose of 107 TCID50. Interestingly, despite a relatively lower cross-neutralization ability, the gD exchange also enabled Bartha-K61 to protect piglets from lethal challenge. In both cases, clinical signs and microscopic lesions were eased, and so was the viral tissue load with the exception of brain. A better protection could be achieved when both gC and gD were swapped in terms of reducing viral load in brain and virus-induced microscopic lesions. Thus, our studies not only revealed individual roles of gC and gD variations in the immune escape and also suggested a synergistic effect of both proteins on induction of protective immunity. These findings have important implications in novel vaccine development for PRV control in China.